Development of novel mechanical diagnostic techniques for early prediction of bone fracture healing outcome - Wolynski, Jakob G., author; McGilvray, Kirk, advisor; Puttlitz, Christian, advisor; Heyliger, Paul, committee member; James, Susan, committee member; Wang, Zhijie, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: diagnostic; non-union; fracture healing; bone fracture